Scared Sick : the Role of Childhood Trauma in Adult Disease - Karr-Morse, Robin; Wiley, Meredith S. (Basic Books, a member of the Perseus Books Group, 2012)
"The first years of human life are more important than we ever realized. In Scared Sick, Robin Karr-Morse connects psychology, neurobiology, endocrinology, immunology, and genetics to demonstrate how chronic fear in infancy and early childhood when we are most helpless lies at the root of common diseases in adulthood. Compassionate and based on the latest research, Scared Sick will unveil a major public health crisis. Highlighting case studies and cutting-edge scientific findings, Karr- Morse shows how our innate fight-or-flight system can injure us if overworked in the early stages of life. Persistent stress can trigger diabetes, heart disease, obesity, depression, and addiction later on"--Provided by publisher.